Entrepreneurial Motivation Among Business Actors: The Role of Entrepreneurship Education and Mentality - Fajriani Azis; Andika Isma (Pinisi Journal of Entrepreneurship Review, 2024)
This study explores the factors influencing entrepreneurial motivation among business actors, specifically focusing on the role of entrepreneurship education and entrepreneurial mentality in Aeoropala Food, Makassar City. The research is classified as quantitative descriptive research, targeting a population of culinary entrepreneurs operating within Aeoropala Food. Data were collected through interviews, questionnaires, and documentation. The analysis involved both descriptive and inferential statistical techniques. The findings reveal that entrepreneurship education plays a critical role in enhancing knowledge and shaping positive attitudes, which in turn boost entrepreneurial motivation. Similarly, an entrepreneurial mentality, characterized by increased risk-taking and self-confidence, is also found to be a significant factor in driving motivation among business actors. The study concludes that the business actors in Aeoropala Food, Makassar City, exhibit a high level of desire, hope, and determination in their entrepreneurial endeavors. The results demonstrate that both entrepreneurship education and entrepreneurial mentality have a simultaneous and significant impact on the entrepreneurial motivation of these business actors, underscoring the importance of these factors in fostering a robust entrepreneurial spirit.